Linking Land Cover to Flood Vulnerability: A Study on Vegetation Indices and Urban Build-Up in Hazard Mapping - Muhammad, Ikhlas Nur; Sarpono, Sarpono; Wibowo, Agus; Setiawibawa, Rachmat; Kurniadi, Anwar (Journal of Geographical Sciences and Education, 2025)
Flooding is the most dominant disaster in Indonesia, with a major case in Greater Jakarta in March 2025, which is the issue of deforestation is highlighted as the main cause of this phenomenon. This study examines the relationship between vegetation canopy and built-up land on flood vulnerability. The analysis was conducted by correlating vegetation and built-up land indices against flood vulnerability maps from the National Disaster Management Agency using the Weighted Overlay method. Results show vegetation has a moderate correlation to flood vulnerability, while built-up land shows a lower correlation. The findings indicate that both contribute to flood risk, but are not a single factor. The study recommends further research with a spatio-temporal approach in smaller areas to be more specific.